2022
DOI: 10.1186/s12889-022-12641-y
|View full text |Cite
|
Sign up to set email alerts
|

The role conflict-burnout-depression link among Chinese female health care and social service providers: the moderating effect of marriage and motherhood

Abstract: Background Women with depression disorder outnumber men, and health care and social service providers are mostly female. Drawing on conservation of resources (COR) theory, this study aims to examine the association between role conflicts and depression among health care and social service providers, and further investigate the mediating effect of burnout, as well as the moderating effect of marital status and motherhood. Methods The data come from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 72 publications
3
13
0
Order By: Relevance
“…This study found that there was a significant positive relationship between role conflict with anxiety and depression. These findings were in consistent with previous studies conducted by Zheng et al [ 42 ], Desouky and Allam [ 46 ], Niedhammer et al [ 31 ] and Nakada et al [ 47 ]. Zheng et al [ 42 ] found that female health care and social service providers experienced a high level of depression.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This study found that there was a significant positive relationship between role conflict with anxiety and depression. These findings were in consistent with previous studies conducted by Zheng et al [ 42 ], Desouky and Allam [ 46 ], Niedhammer et al [ 31 ] and Nakada et al [ 47 ]. Zheng et al [ 42 ] found that female health care and social service providers experienced a high level of depression.…”
Section: Discussionsupporting
confidence: 94%
“…These findings were in consistent with previous studies conducted by Zheng et al [ 42 ], Desouky and Allam [ 46 ], Niedhammer et al [ 31 ] and Nakada et al [ 47 ]. Zheng et al [ 42 ] found that female health care and social service providers experienced a high level of depression. Organizational role conflict was significantly and positively associated with female social workers' depression.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study was conducted among Chinese WLWH. Chinese WLWH react differently to symptom management self-efficacy than men because of their gender roles, as in this traditional culture, women tend to be more responsible for doing house chores, taking care of family members as well as making sure the ends meet [ 36 , 37 ]. Also, WLWH are more likely to be victims of domestic violence and their household responsibilities are heavy, which can compromise their ability to cope with the disease [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation of a latent relationship is provided by the results of a study conducted in a group of women employed in health care. They showed that emotional exhaustion and depersonalization mediate between work-related pressure (WHC) and psychological disorders in working women [ 14 ]. Therefore, taking into account gender and social roles in the search for burnout predictors seems to be a vital research direction.…”
Section: Introductionmentioning
confidence: 99%